2023
DOI: 10.1039/d2sc06234h
|View full text |Cite
|
Sign up to set email alerts
|

Inherently chiral calixarenes by a catalytic enantioselective desymmetrizing cross-dehydrogenative coupling

Abstract: Under the catalysis of PdBr2 and a chiral phosphoramidite ligand, the upper-rim mono (2-bromoaroyl)-substituted calix[4]arene derivatives underwent facile enantioselective desymmetrization reaction to afford the 9H-fluorene-embedded inherently chiral calixarenes in good...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Almost simultaneously, Tong, Wang et al reported another catalytic enantioselective synthesis of inherently chiral calix [4]arenes from the same prochiral substrates 9 using a Pdcatalyzed CÀ H activation desymmetrization strategy [24] (Scheme 5). Interestingly, in the presence of catalytic amount of PdBr 2 and chiral BINOL-derived phosphoramidite ligand L4, the reaction of achiral calix [4]arenes 9 proceeded through the transannular dehydrogenative arene-arene coupling process, leading to a series of 9H-fluorene-embedded inherently chiral calixarenes 13 with good yields and ee values.…”
Section: Catalytic Enantioselective Synthesis Of Inherently Chiral Ca...mentioning
confidence: 99%
“…Almost simultaneously, Tong, Wang et al reported another catalytic enantioselective synthesis of inherently chiral calix [4]arenes from the same prochiral substrates 9 using a Pdcatalyzed CÀ H activation desymmetrization strategy [24] (Scheme 5). Interestingly, in the presence of catalytic amount of PdBr 2 and chiral BINOL-derived phosphoramidite ligand L4, the reaction of achiral calix [4]arenes 9 proceeded through the transannular dehydrogenative arene-arene coupling process, leading to a series of 9H-fluorene-embedded inherently chiral calixarenes 13 with good yields and ee values.…”
Section: Catalytic Enantioselective Synthesis Of Inherently Chiral Ca...mentioning
confidence: 99%
“…13). 29 This new family of intrinsic chiral copirofins has unique chiral optical properties due to the highly rigid structure induced by the 9 H -fluorene segment. Notably, among the numerous new intrinsic chiral calix[ n ]arene prepared, P - 12a and M - 12a exhibited strong CPL activity.…”
Section: Cpl Materials Based On Chiral Macrocyclesmentioning
confidence: 99%
“…10 Recently, this method has been exploited to construct ICC derivatives in asymmetric manner. Intramolecular C–H arylations 11 or transannular, dehydrogenative arene–arene coupling 12 were made accessible in high yields and enantioselectivities by a judicious choice of reaction conditions (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%